Partisipasi Masyarakat dalam Penyelenggaraan Pelayanan Publik - Maani, Karjuni Dt. (Fakultas Ilmu Sosial Universitas Negeri Padang, 2012)
Community participation in public service began in the preparation of service standards to the evaluation and award. Community participation can be embodied in the form of cooperation, fulfillment of rights and obligations of the community, and participation in policy making and shaping public services watchdog. Community participation is an important part of the public service system. Thus the conventional service management that ignores the process of community involvement in public service cannot be maintained anymore. Our concern is to develop an ideal form of participation where the community can be mobilized itself to seek the necessary public services.Kata Kunci: partisipasi masyarakat, lembaga pengawasan, pengguna layanan, pemangku kepentingan, pelayanan publik